2019
DOI: 10.1111/ijfs.14191
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the difference of 4‐hydroxyhexenal and 4‐hydroxynonenal formation in various vegetable oils during thermal processes by kinetic and thermodynamic study

Abstract: Summary The formation of two toxic aldehydes, 4‐hydroxyhexenal (HHE) and 4‐hydroxynonenal (HNE) were monitored in five vegetable oils during thermal processing (100–200 °C) with the results modelled. HHE was only determined in rapeseed and linseed oil, while HNE was determined in all tested oils and the contents varied significantly depending on the oil type. For HHE/HNE‐detected oils, the evolution during heating was well described by the pseudo‐first‐order kinetic model. The equilibrium contents of HHE/HNE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…That suggested that both formation and degradation reactions of GEs were considered to follow the Arrhenius equation (eq ). Previously, the Arrhenius equation has been well used to fit the chemical reaction in food, including the formation of some processing hazards such as aldehyde , and advanced glycation end products. , The calculated A and E a are shown in Table . The E a of k 1 was 34.58 kJ/mol, which was higher than that of k 2 (12.83 kJ/mol).…”
Section: Resultsmentioning
confidence: 99%
“…That suggested that both formation and degradation reactions of GEs were considered to follow the Arrhenius equation (eq ). Previously, the Arrhenius equation has been well used to fit the chemical reaction in food, including the formation of some processing hazards such as aldehyde , and advanced glycation end products. , The calculated A and E a are shown in Table . The E a of k 1 was 34.58 kJ/mol, which was higher than that of k 2 (12.83 kJ/mol).…”
Section: Resultsmentioning
confidence: 99%
“…However, the total aldehyde levels in the CO used for the FCBM were lower than those extracted from the FCBM. The different total levels of the three aldehydes in the oils could be attributed to their varying fatty acid composition (Ma et al , ). Nonetheless, the variation tendencies in terms of the aldehyde levels in the frying oils and fried foods were almost the same (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Camellia oleifera, has about 280 species worldwide, and was as an important source of edible oil for 1000 years. It is mainly used to produce camellia oil, which exhibits very similar fatty acid profiles [1,2] and provides a variety of health benefits, such as prevention of cardiovascular and gastrointestinal diseases [3]. However, with the increasing consumption and production of camellia oils, high contents of insoluble waste by-products also raise rapidly.…”
Section: Introductionmentioning
confidence: 99%